Sexuality in Women After Hysterectomy - Sawitri, Brihastami; Muhdi, Nalini (Jurnal Psikiatri Surabaya, 2020)
Hysterectomy is the most common major gynecological surgeries, with up to 39,4% women will experience it during her lifetime. This procedure can be stressful for women as half of them will experience mild to severe physical and psychological complications. Uterus removal is often associated with de-feminization, castration, being disabled and loss of wholeness which may alter body image and self-esteem, ultimately lead to depression. Most women are anxious on how hysterectomy affect their sexuality, but only few feel comfortable discussing this essential matter to health professionals. The evaluation and management of sexual dysfunction had been the traditional province of psychiatrist. Psychiatrists should fulfill their competencies by updating knowledge on sexuality and sexual dysfunction, improving communication skill, being comfortable with own sexuality and discussing sexuality with other. Pharmacotherapy, relaxation techniques, behavior therapy, group therapy, analytical oriented sex therapy, dual-sex therapy and other techniques or exercises are some modalities option which may help women with sexual difficulties post-hysterectomy.